1998
DOI: 10.1016/s0370-2693(98)00821-1
|View full text |Cite
|
Sign up to set email alerts
|

On the Regge slopes intramultiplet relation

Abstract: We show that only additivity of inverse Regge slopes is consistent with both the formal chiral limit m(n) → 0 and the heavy quark limit M (Q) ≫ M (n), where n = u, d, and m, M are current and constituent quark masses, respectively.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…The paper by Burakovsky and Goldman [42] showed that only the additivity of inverse Regge slopes is consistent with the formal chiral and heavy quark limits for both mesons and baryons, and that the factorization of Regge slopes, although consistent with the formal chiral limit, fails in the heavy quark limit. Besides, in…”
Section: Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…The paper by Burakovsky and Goldman [42] showed that only the additivity of inverse Regge slopes is consistent with the formal chiral and heavy quark limits for both mesons and baryons, and that the factorization of Regge slopes, although consistent with the formal chiral limit, fails in the heavy quark limit. Besides, in…”
Section: Frameworkmentioning
confidence: 99%
“…Also, it saturates the inequality for Regge intercepts [52] which follows from the Schwarz inequality and the unitarity relation. The above two relations are usually generalized to the baryon case [23,42,51], in which one has…”
Section: Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The parameters αii- and αitruei-false(normal0false) are, respectively, the slope and intercept of the trajectory. The intercepts and slopes can be described by [15, 29] αitruei(normal0)+αjtruej(normal0)=normal2αitruej(normal0), normal1αitruei+normal1αjtruej=normal2αitruej. …”
Section: Mass Matrix and Regge Trajectorymentioning
confidence: 99%